2019
DOI: 10.1111/ijlh.13098
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric reference intervals for common coagulation assays in Chinese children as performed on the STA‐R coagulation analyzer

Abstract: Introduction In order to correctly manage the paediatric patients affected with haemostatic disorders, age‐appropriate reference intervals should be used. The purpose of this study was to establish age‐specific reference intervals for prothrombin time (PT), thrombin time (TT), activated partial thromboplastin time (aPTT) and fibrinogen (Fg). Methods In this study, a total of 34 234 apparently healthy children and adolescents aged 0‐15 years were chosen as reference individuals. PT, TT, aPTT and Fg were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Using the STA-R coagulation analyzer (China), HemosIL Assays on ACL TOP Hemostasis Testing Systems (France), and the Sysmex CA-1500 System in parallel with the Behring BCS System using reagents from Siemens (Dutch) lower fibrinogen levels and aPTT as well as TCT prolongation were observed, attributable to decreased concentrations of clotting factors in younger children. 8,10,17 Variable PT RIs are reported in the literature; our findings and results from the Chinese group observing significant differences in PT levels by age contrast with the French study. Potential explanations for observed disparity in PT results between reagents include different sensitivities to factor levels or alternate endpoints (eg, maximum acceleration versus maximum top speed).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Using the STA-R coagulation analyzer (China), HemosIL Assays on ACL TOP Hemostasis Testing Systems (France), and the Sysmex CA-1500 System in parallel with the Behring BCS System using reagents from Siemens (Dutch) lower fibrinogen levels and aPTT as well as TCT prolongation were observed, attributable to decreased concentrations of clotting factors in younger children. 8,10,17 Variable PT RIs are reported in the literature; our findings and results from the Chinese group observing significant differences in PT levels by age contrast with the French study. Potential explanations for observed disparity in PT results between reagents include different sensitivities to factor levels or alternate endpoints (eg, maximum acceleration versus maximum top speed).…”
Section: Discussioncontrasting
confidence: 69%
“…and analyzers. 5,6,[8][9][10]17 However, many pediatric RIs are still derived from adults, often using different laboratory techniques and all are estimated using standard, discrete age groups. 11,13,14 A paucity of literature measures the extent to which results from different technical conditions can be compared.…”
mentioning
confidence: 99%
“…The concentrations of most coagulation proteins vary significantly with age. 9 It was reported that aPTT was prolonged in infants 9 and children 10 compared with adults.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the individuals in the present study were aged from 20 to 79 years old. It was reported that the median time of aPTT and TT was significantly prolonged in all pediatric age groups compared with the adult group in a previous study10 ; therefore, reference values of the individuals aged below 20 years remained to be determined. Finally, due to race-based differences in aPTT,21 the reference range of coagulation assays in a healthy population in the Chaoshan region may be different from that in other populations in China.…”
mentioning
confidence: 93%
“…In addition, results of the coagulation assays are highly age-dependent and must be used to ensure the correct evaluation of coagulation assays in children, especially in the first year of life [ 37 ]. For newborns, coagulation factors are already low and gradually increase to adult levels after 6 months [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%